A 2D volume conservative numerical model of hydraulic fracturing. (1st April 2017) - Wangen, Magnus
Highlights: Volume conservative numerical model for hydraulic fracturing. Makes use of regular grids on a reservoir scale (no special gridding). A new critical fluid pressure for fracture propagation. Analytical models for hydraulic fracturing of homogeneous and impermeable rock. Numerical examples of hydraulic fracturing of in inhomogeneous and permeable rocks. Abstract: A volume conservative numerical approach is suggested for the modelling of propagation of a hydraulic fracture away from an injection well. A regular finite element grid is applied at the reservoir scale without any special gridding of the fracture. Models for critical fluid pressure are used to derive exact solutions for the propagation of hydraulic fractures in impermeable and homogeneous rocks. The numerical model is verified by these exact solutions for hydraulic fracturing. Numerical examples of hydraulic fracturing of permeable and inhomogeneous rocks are given, where the volume balance is given as a function of time.